(untitled) (Jurnal Adabiya, 2020)
Tragedy is a negative word, describing an unwanted event that still occurred; the negatifity of tragedy is seen form the destructive effect it caused such as destruction, death, and disappointment. This paper try to address tragedy not just from the negative side but from the starting point of tragedy from point of view Friedrich Nietzsche, Nietzsche sees tragedy originally derived from the theatre of art, between visual art such as sculpture and non visual art such as music, this paper uses descriptive analytic with main focus on the book of Nietzsche The Birth of Tragedy, to find the contect of tragedy in the world of arts specifically and culture generally.